The Utilization of Vegetable Waste Silage as Feed Ingredient in Diets for Tilapia Oreochromis niloticus. (November 2019) - Putra, A N; Jaenudin,; Sofia, F; Mustahal,; Syamsunarno, M B; Hermawan, D; Herjayanto, M
Abstract: The vegetable waste silage is potential as a feed ingredient for tilapia culture. Silage is a product of the processing of materials by the addition of acid or by anaerobic fermentation. This study aimed to evaluate the effect of vegetable waste silages on the growth of tilapia ( Oreochromis niloticus ). Formic acid is used in this study as organic acid for the preservative. Four diets concentration of formic acid in making silage (0%, 3%, 4%, and 5%) was formulated containing 27% crude protein. The result showed that total digestibility, protein digestibility, and fat digestibility were significantly higher (P<0.05) in 4% formic acid and 5% formic acid than Control. The value of growth was significantly highest (P<0.05) in 5% formic acid (2.96±0.08 %/day), followed by 4% formic acid (2, 66±0, 14 %/day), 3% formic acid (2, 56±0, 05 %/day) and control (2, 54±0, 21 %/day). The utilization of 5% formic acid in making vegetable waste silage showed the best result on growth and feed efficiency than the other treatments.